Importance of using GIS technologies in soil science - Shamuratova Maftuna Gulimmat qizi; Duschanova Oygul Farxodovna; Saparbayev Zakir Yusubboyevich (Zien Journals, 2023)
The reason we focus on this concept in this book is because information is an important part ofGAT, or without it, GAT would be meaningless. We can call it information in our ordinary language, but ifwe say it in the language of GAT, then this concept has a slightly wider meaning. We know that in the worldof information there are 2 different concepts, one is information and the other is information. Informationis the event we see, and information is the image of that event processed in the human mind. In GAT,information is derived from the processing of primary data obtained from the place, unlike the abovedefinition, this information or primary information is not in the human mind, it is processed using specialprograms of GAT and stored in the database, and in the future, depending on the user's desire, it is presentedin the form of electronic or ordinary paper.
Keywords: Geodata; model; photogrammetry; modeling; grid